Isolation and Identification of Mercury-Resistant Fungi as Bioremediation Agents from Gold Mining - Sahana, Laudy Arrisa Arumsari; Mohamad , Yani; Rohani Cinta Badia Br , Ginting (Universitas Brawijaya, 2024)
To overcome the pollution problem due to the accumulation of heavy metal Hg, a clean-up or remediation effort is needed from the former landfill for hazardous and toxic waste. In this research, bioremediation experiments will be conducted by inoculating fungi culture that is already known to have the potential to absorb heavy metals Hg. Samples of soil contaminated with heavy metals Hg taken from the tailings of gold mining owned by the people in Kertajaya Village, Simpenan District, Sukabumi Regency. The stages of this study consisted of isolation of fungi, purification and morphology of fungi isolate, screening of fungi isolate, qualitative screening of fungi for ligninolytic activity (laccase), and molecular identification of the isolated fungi. The results of the screening showed that three isolates of potential fungi coded M.2, M.10, and M.13 were able to grow with a mercury concentration of 350 ppm, while one isolate coded R4.28 reached a concentration of 1000 ppm. In addition, isolate M.2 was selected as the best strain compared to isolates M.10, M.13, and R4.28 for the qualitative test of laccase production in ligninolytic enzymes. Based on the molecular analysis of the 18S rRNA gene, M.2 isolates were similar to Trichoderma yunnanense, which was strengthened by a similarity value of 99.66%. Isolate R4.28 was similar to Penicillium soli, which was strengthened by a similarity value of 99.32%.